Conceptualizing a framework for slow tourism in a rural destination in Malaysia - Farah Atiqah, M. N. *; Vikneswaran, N.; Mura, Paolo (American Scientific Publishers, 2015)
There is a growing belief to change the fast-paced tourism activities to a slower pace in order to appreciate the beauty of slowing down during vacations. The image of rural destinations is socially constructed to have a slower level of consumption than urban destinations. Therefore, there is a possibility that rural destinations are an idealistic setting or landscape to facilitate slow tourism aside from urban destinations. This study is looking into initiating the slow tourism conceptual framework to investigate the suitability of pursuing slow tourism activity in a rural destination. The objective was obtained through the method of thematic analysis of slow tourism literatures in order to construct an ideal framework that can be used for slow tourism. The findings from the study can be proposed as an initial guide for the local authority to position slow tourism as one of the attractions of rural destinations.